2015
DOI: 10.1007/s10494-015-9632-2
|View full text |Cite
|
Sign up to set email alerts
|

Time-accurate Numerical Simulations of Swirling Flow with Rotor-stator Interaction

Abstract: A series of numerical simulations is undertaken to study a highly swirling turbulent flow generated by rotor-stator interaction in a swirl generator. The purpose is to assess the applicability of different turbulence models in swirling flow with a high level of unsteadiness and a significant production and dissipation of turbulence in the flow away from the wall. Nine turbulence models are compared: four high-Reynolds URANS, two low-Reynolds URANS and three hybrid URANS-LES. These are the standard k − , SST k … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The flow in water turbines operating at the best efficiency point condition has a moderately low level of swirl forming a stable on-axis structure (Javadi, Bosioc, Nilsson, Muntean, & Susan-Resiga, 2016;Javadi & Nilsson, 2015a). The flow at conditions away from the best efficiency point often contains a high level of swirl which may cause a recirculation region.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The flow in water turbines operating at the best efficiency point condition has a moderately low level of swirl forming a stable on-axis structure (Javadi, Bosioc, Nilsson, Muntean, & Susan-Resiga, 2016;Javadi & Nilsson, 2015a). The flow at conditions away from the best efficiency point often contains a high level of swirl which may cause a recirculation region.…”
Section: Introductionmentioning
confidence: 99%
“…Javadi and Nilsson (2014a) studied the Scale-Adaptive Simulation (SAS) (Menter & Egorov, 2010) approach in highly swirling flows and reported that the approach predicts the massively separated swirling flows very well. Detached-Eddy Simulation (DES) (Spalart, Jou, Strelets, & Allmaras, 1997) is another promising hybrid URANS-LES strategy which is studied for application to swirling flows (Javadi & Nilsson, 2015a, 2015bJavadi et al, 2016). The Delayed DES (DDES) methodology was proposed by Spalart et al (2006) to identify the boundary layer thickness and to extend the URANS mode compared to that of the initially proposed DES methodology.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations